Perceptions of Why Women Stay in Physically Abusive Relationships: A Comparative Study of Chinese and U.S. College Students - Pugh, Brandie (Journal of interpersonal violence, 2021)
In both China and the United States, public attitudes toward intimate partner violence (IPV) have shifted from viewing IPV as a tolerable, private matter to viewing it as a matter of public concern that should be dealt with as a crime. Empirical and comparative examinations of the perceptions of why women stay in physically abusive relationships are lacking. Answering this question calls for comprehensive, methodologically rigorous research. Using survey data collected from approximately 1,000 college students from two Chinese and two U.S. universities, this study empirically compared and contrasted factors that impact U.S. and Chinese students’ perceptions as to why women remain in physically abusive relationships. Utilizing a theoretical framework of social constructionism, two common reasons were assessed: Women stay in physically abusive relationships because of learned helplessness and positive beliefs in the relationship/hope for the future. The results show that viewing IPV as a crime, gender, and beliefs of the causes of IPV were robust predictors of college students’ perceptions toward why women stay in physically abusive relationships. U.S. college students were more likely to express sympathy and understanding toward why women remain in abusive relationships than Chinese students. Directions for future research and policy implications were discussed.